1994
DOI: 10.1002/j.2161-007x.1994.tb00836.x
|View full text |Cite
|
Sign up to set email alerts
|

Religious Counseling: To Be Used, Not Feared

Abstract: Our society is placing more emphasis on religion and religious issues. Persons seeking counseling often request Christian counseling. Students in academic settings often express an interest in becoming Christian counselors. Often the religious aspect is left out or avoided in courses for training counselors. This article gives some specific ways in which religious issues can be used in a counseling setting using the three ps: place, personhood and philosophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…If marriage counselors are going to help couples access these resources, they must be trained to do so. Mattson (1994) stated that society is placing more emphasis on religious issues, that some clients are requesting Christian counseling, and that some students in academic settings are expressing an interest in being trained as Christian counselors; however, the religious aspect is often left out or avoided in courses for training counselors. Although Christian counseling only addresses one religious perspective, a more encompassing perspective by Pate and Bondi (1992) is that the question for counselor educators is not whether religious beliefs in general will be an important part of the focus on client diversity in graduate counseling programs, but how to include counselors' consideration of clients' religious values in the curriculum.…”
Section: Resultsmentioning
confidence: 99%
“…If marriage counselors are going to help couples access these resources, they must be trained to do so. Mattson (1994) stated that society is placing more emphasis on religious issues, that some clients are requesting Christian counseling, and that some students in academic settings are expressing an interest in being trained as Christian counselors; however, the religious aspect is often left out or avoided in courses for training counselors. Although Christian counseling only addresses one religious perspective, a more encompassing perspective by Pate and Bondi (1992) is that the question for counselor educators is not whether religious beliefs in general will be an important part of the focus on client diversity in graduate counseling programs, but how to include counselors' consideration of clients' religious values in the curriculum.…”
Section: Resultsmentioning
confidence: 99%
“…Ancak; bu teolojik vurgunun Hıristiyan geleneğine ait bir kavramla yapılmasının diğer dinler bağlamında gerçekleştirilecek bir hizmet için sorun oluşturabileceği de bilimsel literatürde tartışılmaktadır. Bu doğrultuda son yıllarda inançsal dışlayıcılıktan kurtulmak amacıyla "pastoral" kavramı yanında "insan varoluşuna dair temel problemlere odaklanan sistem" (Worthington, 1986, s.421;Bullis ve Mazur, 1993;Mattson, 1994;Dombeck, 1998, s.362) anlamına gelen "religious" kavramı da tercih edilmektedir (Doehring, 2015, s.23). Tercih her ikisinden hangisi olursa olsun yine de mesleğin teolojik yönüne vurgu değişmemektedir.…”
Section: Batıda Dinî Danışmanlığın Kavramsal Serüveniunclassified
“…A third consideration of spiritual issues in counseling is how to determine when and where spiritual issues should be addressed. One may consider spiritual issues arising from the following points of reference: client initiation, counselor initiation, counseling interventions (Hinterkopf, 1994), counseling relationship, and work setting (Mattson, 1994). Peck (1993) suggested that counselors initiate questions about the client's religious background, and Bishop (1 992) outlined guidelines for counselors to educate themselves on religious values in counseling.…”
Section: Spiritual Issues In Counselingmentioning
confidence: 99%